Статистические модели механико-технологических свойств очесанного вороха озимой пшеницы - Кюрчев, С. В.; Леженкин, И. А.; Кюрчев, С. В.; Леженкін, І. О.; Kiurchev, Sergey; Lezhenkin, Ivan (КНТУ, 2013)
В статье приводятся статистические модели в виде распределений случайных величин механико-технологических свойств очесанного вороха зерновых, а также дается их статистический анализ. В статті наводяться статистичні моделі у вигляді розподілів випадкових величин механіко-технологічних властивостей обчісаного вороху зернових, а також дається їх статистичний аналіз. To build statistic models of mechanical and technological properties of winter wheat combed heap. A field experiment was carried out to obtain combed heap. A harvesting aggregate included a wheeled tractor, trailed harvesting machine and a trailer for combed heap gathering. The harvester passed a test plot of land. Then the aggregate stopped and fifty samples have been chosen to define density of the combed heap breakup. Later the samples were sorted out and the primary information about the percentage of every component content was obtained. The primary information has been processed by the probability theory and mathematical statistics methods. Consequently main statistic characteristics of every component content, statistic models in the form of distribution laws of random variables have been got. The same information was obtained for the combed heap. It was ascertained that the value of the combed heap components content and its density obeyed to the normal distribution law of random variables. The check according Pirson criterion showed that all the received models are adequate.
Статистичні моделі механіко-технологічних властивостей обчісаного вороху озимої пшениці
Statistic models of mechanical and technological properties of winter wheat combed heap
Keywords: статистическая модель; статистические характеристики; плотность распределения случайных величин; очесанный ворох; озимая пшеница; фракционный состав; плотность вороха; статистична модель; статистичні характеристики; щільність розподілу випадкових величин; обчісаний ворох; озима пшениця; фракційний склад; щільність вороху; statistic model; statistic characteristics; the density of random variables distribution; breakup; heap density; winter wheat